The Conceptual Re-Edification of Strict Non-Contractual Liability - Fernández Cruz, Gastón (2005)
In Peru, article 1970 of the Civil Code establishes a regime of strict liability, referring to risk and exposure to danger as criteria of imputation, thus disregarding fault. This position marks a departure from the generally accepted rules, as it establishes a strict liability clause alongside a traditional general liability clause based on fault. The inclusion of strict liability in the Peruvian Civil Code responds to the recognition of modern needs, characterised by new forms of risk and damage. In this context, the authors face the challenge of unravelling the complexity of strict liability in tort in Peruvian civil law. Among the aspects analysed is the distinction between strict liability 'for risk' and strict liability 'for exposure to danger'. It also discusses the relevance of designating certain assets as 'risky' or 'dangerous' and questions the appropriateness of such concepts. In conclusion, this work makes a significant contribution to the understanding of the scope and limits of strict liability in tort in the Peruvian legal system, providing an illuminating view of its application.